Individual Choice or Policies? : Drivers of Female Employment in Europe - Christiansen, Lone Engbo; Lin, Huidan; Pereira, Joana; Topalova, Petia (Washington, D.C. : International Monetary Fund, 2016)
Female labor force participation has increased markedly in many European countries during the past decades. Nonetheless, participation rates remain low in some economies, and a significant gender gap persists in most countries. Using micro-level data to control for factors that influence personal choice, we re-examine the determinants of female employment in Europe. The results highlight the importance of positive attitudes towards women working and individual characteristics such as years of education and number of children. However, even after controlling for these factors, policies are also key drivers of female employment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet